Healthy School Environment and its Impact on Students' Health: A Case from Community Schools at Pokhara Metropolitan City - Tripathi, Krishna Prasad; Acharya, Devaraj (Education and Development, 2021)
A healthful school environment plays a vital role in students' health. The study aims to assess the status of healthful school living, and its impact on students' health in Pokhara Metropolitan City using the descriptive and analytical study design. We choose 120 samples randomly from 12 clusters of the Resource Center of District Education Coordination Unit, Kaski. Five boys and five girls were selected from class nine or ten randomly. The interview schedule was used to collect data from the students and an observation checklist was used to find out the real situation. The majority [10 out of 12] schools had volleyball courts but the students practiced games once a week in the sports meet program only. It was found that the schools had canteen facilities with limited services; only certain snacks were avaible. The highest 37.7 percent was of the students were found commonly suffering from headaches. Similarly, 16 percent of the students experienced laziness due to the lack of fresh air in the class, whereas 10 percent of them felt difficult to see due to long-distance or deem light in the classroom. Only 8.7 percent of the students felt tired and nearly six percent had fever and vomiting. Some other problems were diarrhoea, abdominal pain, nausea, obesity, difficulty breathing, and sore throat that were under five percent. The management should consider that physical facilities according to the students' level and interests will make the student feel comfortable and help them to be healthy and wise.